Pengaruh Motivasi Kerja Dan Kompensasi Terhadap Kinerja Karyawan Pada PT. BFI Finance Cabang Jakarta - Safuan, Safuan; Zikri, Afdhalul (GEMA EKONOMI, 2023)
The research objective was ro determine the effect of work motivation and motivation on employee performance at PT BFI Finance. This type of research is quantitative. The sample involved in the study was 30 employees, and the sample used was simple random sampling. In collecting data, researchers used observation, questionnaires, and documentation. Data analysis techniques used in this research are descriptive statistical analysis, correlation, and simple regression. Based on simple correlation and regression, the research results show that work motivation and compensation have a significant effect on employee performance at PT BFI. Work motivation and compensation variables have an influence and relationship with employee performance variables